COMMUNITY ONLINE COMPLAINT SYSTEM (SIPENGOL) - Septian Nasution, Andri; Harahap, Boy Endar Muda; Sanjaya , Dimas; Huwaidi , Hafizh; Kurniawan, Fahmi (Cattleya Darmaya Fortuna, 2024)
The web-based community complaint system is designed to improve the quality of public services by facilitating the reporting of complaints and suggestions from the public effectively and efficiently. The system utilizes web technology to allow the public to report complaints and suggestions online, thus facilitating the reporting process and speeding up the response time. The system has features such as complaint reporting, status tracking, feedback, and data analysis to assist the government and relevant agencies in identifying and resolving problems. Thus, this system can increase public satisfaction, transparency, and public participation in the improvement of public services. This research uses qualitative and quantitative research methods to develop and test the system. The results show that a web-based public complaint system can improve the quality of public services and satisfy the needs of the community. Therefore, this system can be used as an effective solution to improve the quality of public services in Indonesia